Human antibodies in Mexico and Brazil neutralizing tick-borne flaviviruses - Cervantes Rincón, Tomás; Kapoor, Tania; Keeffe, Jennifer R; Simonelli, Luca; Hoffmann, Hans-Heinrich; Agudelo, Marianna; Jurado, Andrea; Peace, Avery; Lee, Yu E; Gazumyan, Anna; Guidetti, Francesca; Cantergiani, Jasmine; et al. (Cell reports, 2024)
Flaviviruses such as dengue virus (DENV), Zika virus (ZIKV), and yellow fever virus (YFV) are spread by mosquitoes and cause human disease and mortality in tropical areas. In contrast, Powassan virus (POWV), which causes severe neurologic illness, is a flavivirus transmitted by ticks in temperate regions of the Northern hemisphere. We find serologic neutralizing activity against POWV in individuals living in Mexico and Brazil. Monoclonal antibodies P002 and P003, which were derived from a resident of Mexico (where POWV is not reported), neutralize POWV lineage I by recognizing an epitope on the virus envelope domain III (EDIII) that is shared with a broad range of tick- and mosquito-borne flaviviruses. Our findings raise the possibility that POWV, or a flavivirus closely related to it, infects humans in the tropics.
Keywords: protilátky virové; Brazílie; viry klíšťové encefalitidy; Antibodies, Neutralizing; Humans; Epitopes; monoklonální protilátky; zvířata; Antibodies, Viral; flaviviruses; neutralizující protilátky; Encephalitis Viruses, Tick-Borne; Antibodies, Monoclonal; klíšťata; epitopy; mužské pohlaví; antibodies; Ticks; tick diseases; Mexiko; ženské pohlaví; Brazil; CP: Immunology; Animals; lidé; Flavivirus; Mexico; Male; Female